Zróżnicowanie innowacyjności europejskiej przestrzeni regionalnej - Strahl, Danuta (Diversification of Innovation in the European Regional Space, 2008)
The article presents the analysis of innovation with reference to regions of European Union member countries using five basic characteristic attributes: the share of employed tertiary education graduates in the total population number aged 25-64, share of continuing education participants in the total population number aged 25-64, number of EPO patents per one million of labour force, share of the employed in services "based on knowledge" as % of total employment in services, share of high and mid-tech industry employment in the total number of industry employees. 240 regions of 25 European Union countries representing NUTS 2 level were covered by the research. 10 European regions which are characterized by best values of attributes were presented as well as 10 regions ranked as last with regard to the studies components. Additionally the article presents the position of Polish regions in the European regional space with regard to values of attributes which illustrate innovation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 30-42